AI-Powered Enterprise Routing Systems: A Technical Deep Dive - Nandini Suresh Kumar (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
This technical article explores the integration of artificial intelligence in enterprise routing systems, presenting a comprehensive examination of system architecture, data infrastructure, monitoring capabilities, and user experience design. The discussion encompasses critical aspects of implementing AI-powered routing solutions, including workflow orchestration, data quality management, observability frameworks, and security considerations. The article delves into how organizations can leverage advanced machine learning techniques to optimize resource allocation, enhance system reliability, and improve operational efficiency while maintaining robust security measures and regulatory compliance. The article highlights the importance of human-centered design approaches and the critical role of AI transparency in fostering user trust and system adoption.